A preliminary review on design conservation of Mughal mosque architecture in Dhaka: a case study between Khan Muhammad Mridha mosque and Rasulullah’s (PBUH) prototype mosque in Madina - Ahmed Dilkhosh, Aurobee; Mohd Nawawi, Norwina; Salleh, Nurul Hamiruddin (Asian Research Publishing Network (ARPN), 2017)
Mughal architecture reigned supreme in the Indian Sub Continent including Bangladesh for over five and half centuries from 12th -18th Century. Home to the fourth largest Muslim population in the world of about ninety percent of the total population, the Mughals had left many relics including mosques for the Muslims. The capital city of Bangladesh, Dhaka, is studded with mosques of Mughal Period and aptly regarded as ‘the City of Mosques' as the same level as Cairo or Istanbul [2]. However, majority of these mosques have disappeared, in ruins, preserved or repaired by giving a modern look, thus giving an impression that conservation of this invaluable 400 years mosque heritage of Dhaka has always been ignored. This paper analysed the current state of architectural conservation of Mughal mosque architecture in Dhaka through a historical review of existing literature with Khan Mohammad Mridha Mosque as the conservation case study. The prototype mosque of Rasulullah (PBUH), the An-Nabawi, in Madinah, Saudi Arabia, is used as a reference for this study to provide guidelines on the extent of conservation to historical mosque-in-use in the light of needs to accommodate the worshippers with the modern requirements. With the limitation of written literature on Dhaka's architectural history and access to sites, the study had identified characteristics of Dhaka's Mughal mosque architecture as heritage traits and had compared them to newly conserved Mughal mosques of its authenticity. Findings on design authenticity of the conserved mosque denote the absence of essential details and characteristics of the Mughal. Constant debate in deciding what needs to be conserved and what had to adapt to meet modern needs between conservators and as practicing Muslim never ends. This preliminary study provides recommendations as a balanced guide for conservators and architects in dealing with heritage mosque as modern buildings.